Employee motivation as an indicator of the desire to continue working: evidence from SMEs in Bangladesh - Hasan Polas*, Mohammad Rashed; Afroz, Rafia; .,, Md Muhibbullah; Sadekin, Md Nazmus (Inderscience Publishers, 2021)
The purpose of this study is to explore how employee motivation factors impact on the employee’s desire to keep working in SME firms. This study primarily is based on raw data which are collected from 278 employees of SME firms in Bangladesh. Apart from adopting the quantitative method, the Smart PLS 3.0 and SPSS V23 were utilised for analysing the gathered primary data. Furthermore, we predicted ten hypotheses in this study. Our findings assure that a positive and significant relationship among working conditions, salary and incentive, and job stability with employee motivation is sustained which indicates a direct relationship on the desire of employees to continue working in this sector. This study did not find any conventional relationship between the behaviour of presidents and subordinates with employee motivation. This study further demonstrates that employee motivation does not mediate the relationship between behaviour of presidents and subordinates with the desire to continue working.